2015
DOI: 10.3109/0284186x.2015.1028590
|View full text |Cite
|
Sign up to set email alerts
|

ART for head and neck patients: On the difference between VMAT and IMPT

Abstract: ART showed benefits for both modalities. However, as IMPT is more conformal, the magnitude of dosimetric changes was more pronounced compared to VMAT. Large anatomic variations had a severe impact on treatment plan quality for both VMAT and IMPT. ART is justified in those cases irrespective of treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…A limitation of the presented analysis is the use of nominal dose distributions. As Müller et al ( 40 ) and Góra et al ( 41 ) showed, IMPT treatment plans are more prone to dose distortions originating from anatomical changes of the patients. Such changes can decrease the dose conformity to the target volume and thus deteriorate the TCP.…”
Section: Discussionmentioning
confidence: 96%
“…A limitation of the presented analysis is the use of nominal dose distributions. As Müller et al ( 40 ) and Góra et al ( 41 ) showed, IMPT treatment plans are more prone to dose distortions originating from anatomical changes of the patients. Such changes can decrease the dose conformity to the target volume and thus deteriorate the TCP.…”
Section: Discussionmentioning
confidence: 96%
“…This allows for an increased dose to the tumor at a reduced integral dose to the normal tissue and organs at risk (OAR) with respect to conventional photon therapy. Two of the indications potentially benefiting from the more conformal dose distributions in IMPT are tumors in the head and neck (H&N) region, [3][4][5] as well as tumors of the prostate. [6][7][8] However, enhanced conformity comes along with an increased sensitivity to anatomical variations during the course of fractionated treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The way of adaptive treatment planning and dose accumulation in A-IMXT and A-IMPT has been based on the method previously described by Goras et al 18 and is illustrated in Fig. 1.…”
Section: A-impt Planningmentioning
confidence: 99%